Islamic Ethics in Tiktok Dynamics: Critical Analysis in Medan Denai District - Lubis, Maryam Khodimatullah; Rubino, Rubino; Ritonga, Elfi Yanti (Journal La Sociale, 2024)
This research aims to analyze the perceptions and practices of TikTok users in Medan Denai District, North Sumatra, in relation to Islamic communication ethics. This research adopts a qualitative approach with a case study method, using in-depth interviews and participant observation. Through analysis of Islamic Mass Communication Ethics theory, this research explores how the young generation in Medan Denai District practices values such as honesty, accuracy of information, and responsibility in their interactions on TikTok. The research results show that the young generation in Medan Denai actively uses TikTok as a means of creative expression and social interaction. They demonstrate a high awareness of Islamic ethical principles, which is reflected in their habit of verifying information before sharing it and in providing honest and constructive comments. This study concludes that TikTok is not only an entertainment platform, but also plays an important role in the formation of ethical values and social interactions in local communities, providing valuable insights for the development of educational policies and communication practices in the digital era.